An overview of yeast cell wall proteins and their contribution in yeast display system - Hossain, SK Amir; Rahman, SM Rifat; Ahmed, Toufiq; Mandal, Chanchal (Asian Journal of Medical and Biological Research, 2020)
Yeast surface display has become an increasingly popular tool for protein engineering and library screening applications. Although, recent advances have greatly expanded the capability of yeast surface display, the protein display system is still far away from industrial application. One of the major components of a stable, efficient and successful yeast surface display system is cell wall anchor protein with which our desired foreign protein will be attached. We studied 80 different yeast cell wall anchored proteins originated mostly from Saccharomyces cerevisiae and Candida albicans. We studied in details all the cell wall proteins in order to find out suitable cell wall proteins to recommend for the researchers to use in the construction of yeast display system. We considered selective physical properties of different yeast cell wall proteins that are crucial for selecting best suited cell surface anchor proteins which are molecular weight, binding domain of anchor protein, length of amino acid and fusion site. Finally, our studies showed that Ccw11, Ccw12. Cwp1, Cwp2, Dan1, Gas1, Gas5, Exg1, Ycr89, Ecm33, Pga4, Sap9, Sap10, Pst1, Pir1, Pir2, Pir3, Pir4, Cis1, Scw4, Scw6, Bgl2, Uth1, Scw1 are the promising and suitable cell wall anchor proteins could be used in construction of yeast cell surface display system. Additionally, this review presents detailed information about all the cell wall proteins in a single work. The future researchers in this field will be able to construct more efficient yeast display system for recombinant protein production at industrial scale using the knowledge presented in this work. Asian J. Med. Biol. Res. June 2019, 5(4): 246-257